A new calibration method between an optical sensor and a rotating platform in turbine blade inspection. (2nd February 2017) - Li, Wen-Long; Wu, An; Li, Zi-Cheng; Zhang, Gang; Yu, Wen-Yong
Abstract: Thin-walled turbine blades with complex features are a critical part of an aviation engine, and a small change in their geometric shape can erode the performance of the aviation engine. Inspecting the blade with an optical device is a promising technique. One key task involved is the calibration of the optical sensor with the rotating platform. This paper presents a novel calibration method for the optical inspection of the blade. Three target spheres are measured by a high-precision laser tracker and an optical sensor. The positions of the sphere centers are used to build a coordinate system and an approximated plane. Following that, the rotation axis and the rotation center of the rotating platform are easily calculated. According to a direction vector from the measured stripe, the transformation parameters between the optical sensor and rotating platform are further calculated. This calibration method is simple to carry out, and it guarantees that all the measured points are represented in the same coordinate system for subsequent parameter extraction and profile error evaluation of the blade surface. The experiments demonstrate the feasibility of the proposed method, and it found that the measurement error after calibration is within 0.02 mm.